Impact of Social Capital on Innovation Performance: The Mediating Role of Learning and Strategic Orientations - Ahsan, Nirmal; Hafeez, Muhammad Haroon (Pakistan Journal of Humanities and Social Sciences, 2023)
Taking into consideration the Resource Based View (RBV) Theory and the Social Capital Theory (SCT), this research investigates how the software industry utilizes strategic resources to surpass innovative performance. This study adopted survey questionnaires to gather particulars from 780 mamagers and owners employing in the software industry in Pakistan. The accumulated information was assessed by employing SPSS and structural equation modeling (SEM) to probe designed hypotheses. We uncovered that social capital influences innovative performance. Furthermore, social capital also affects the technological and learning orientation of the software industry. Moreover, technological orientation and learning orientation both mediate the impact of social capital on innovative performance. The crucial beneficence of the research is to enrich and extend the RBV, SCT, and literature regarding innovation in the domain.